High Concentrations of Nitric Oxide Inhalation Therapy in Pregnant Patients With Severe Coronavirus Disease 2019 (COVID-19). Issue 6 (December 2020) - Safaee Fakhr, Bijan; Wiegand, Steffen B.; Pinciroli, Riccardo; Gianni, Stefano; Morais, Caio C. A.; Ikeda, Takamitsu; Miyazaki, Yusuke; Marutani, Eizo; Di Fenza, Raffaele; Larson, Grant M.; Parcha, Vibhu; Gibson, Lauren E.; et al.
Abstract : BACKGROUND: Rescue therapies to treat or prevent progression of coronavirus disease 2019 (COVID-19) hypoxic respiratory failure in pregnant patients are lacking. METHOD: To treat pregnant patients meeting criteria for severe or critical COVID-19 with high-dose (160–200 ppm) nitric oxide by mask twice daily and report on their clinical response. EXPERIENCE: Six pregnant patients were admitted with severe or critical COVID-19 at Massachusetts General Hospital from April to June 2020 and received inhalational nitric oxide therapy. All patients tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. A total of 39 treatments was administered. An improvement in cardiopulmonary function was observed after commencing nitric oxide gas, as evidenced by an increase in systemic oxygenation in each administration session among those with evidence of baseline hypoxemia and reduction of tachypnea in all patients in each session. Three patients delivered a total of four neonates during hospitalization. At 28-day follow-up, all three patients were home and their newborns were in good condition. Three of the six patients remain pregnant after hospital discharge. Five patients had two negative test results on nasopharyngeal swab for SARS-CoV-2 within 28 days from admission. CONCLUSION: Nitric oxide at 160–200 ppm is easy to use, appears to be well tolerated, and might be of benefit in pregnant patients with COVID-19 with hypoxic respiratory failure. Abstract : High-dose nitric oxide is a novel treatment associated with improved oxygenation and decreased tachypnea in pregnant patients with severe coronavirus disease 2019 (COVID-19).